Structure-guided design of cell wall biosynthesis inhibitors that overcome β-lactam resistance in Staphylococcus aureus (MRSA). - Contreras-Martel, C; Amoroso, A; Woon, E; Zervosen, A; Inglis, S; Martins, A; Verlaine, O; Rydzik, A; Job, V; Luxen, A; Joris, B; Schofield, C; et al. (2011)
β-Lactam antibiotics have long been a treatment of choice for bacterial infections since they bind irreversibly to Penicillin-Binding Proteins (PBPs), enzymes that are vital for cell wall biosynthesis. Many pathogens express drug-insensitive PBPs rendering β-lactams ineffective, revealing a need for new types of PBP inhibitors active against resistant strains. We have identified alkyl boronic acids that are active against pathogens including methicillin-resistant S. aureus (MRSA). The crystal structures of PBP1b complexed to 11 different alkyl boronates demonstrate that in vivo efficacy correlates with the mode of inhibitor side chain binding. Staphylococcal membrane analyses reveal that the most potent alkyl boronate targets PBP1, an autolysis system regulator, and PBP2a, a low β-lactam affinity enzyme. This work demonstrates the potential of boronate-based PBP inhibitors for circumventing β-lactam resistance and opens avenues for the development of novel antibiotics that target Gram-positive pathogens.